The Influence of Digital Training, Culture, Organization, and Competence on Employee Performance through Organizational Commitment as an Intervening Variable - Hakim, Khoirul Umam; Efendi, Suryono (Jurnal Manajemen dan Inovasi (MANOVA), 2025)
Objective – The purpose of the study was to examine the effect of digital training, organisational culture, competence on employee performance through organisational commitment. Design/methodology/approach – Quantitative research method by distributing questionnaires to 133 employees of the Bangkalan Regency Trade Office. The data analysis technique is Structural Equation Modelling (SEM) with Partial Least Square (PLS). Findings – Digital training and organizational culture have a positive and significant influence on Organizational Commitment and Employee Performance at the Bangkalan Regency Trade Office, while competence has no significant influence on either variable. Research limitations/implications – This research was conducted at the Bangkalan Trade Office, focusing on Digital Training, Culture, Organization, and Competence on Employee Performance Through Organizational Commitment as an Intermediary Variable. The researchers also suggest exploring other variables that influence employee performance. Practical implications – This study is expected to encourage the Bangkalan Regency Trade Office to improve employee performance through the implementation of digital training and a strong organizational culture, as well as to increase employee commitment to the organization. The importance of this training can serve as a reference for other companies in improving employee performance. Originality/value – This study provides new insights into the impact of Digital Training, Culture, Organization, and Competence on Employee Performance Through Organizational Commitment as an Intermediary Variable. The originality of this study lies in its focus on digital training, organizational culture, and competence on employee performance in the Bangkalan district trade office.